2020
DOI: 10.1002/cctc.201901434
|View full text |Cite
|
Sign up to set email alerts
|

Post‐synthetic Modification of DUT‐5‐based Metal Organic Frameworks for the Generation of Single‐site Catalysts and their Application in Selective Epoxidation Reactions

Abstract: New single‐site catalysts based on mixed‐linker metal‐organic frameworks with DUT‐5 structure, which contain immobilized Co2+, Mn2+ and Mn3+ complexes, have successfully been synthesized via post‐synthetic modification. 2,2’‐Bipyridine‐5,5’‐dicarboxylate linkers were directly metalated, while 2‐amino‐4,4’‐biphenyldicarboxylate linkers were post‐synthetically modified by their conversion to Schiff‐base ligands and a subsequent immobilization of the metal complexes. The resulting materials were used as catalysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 58 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…MOF-253 was synthesized through solvothermal reactions between Al­(NO 3 ) 3 ·9H 2 O and H 2 bpydc (Figure A). Powder X-ray diffraction (PXRD) studies demonstrated the synthesis of MOF-253 as crystalline white powders, and thermal gravimetric analysis (TGA) supported the chemical formula of Al­(OH) (bpydc) (Figure S2). The treatment of MOF-253 with FeCl 2 in tetrahydrofuran afforded the pre-catalyst 1-pre , which was suspended in methanol and oxidized under an O 2 atmosphere to give the MOF catalyst 1 (Figure B).…”
Section: Resultsmentioning
confidence: 95%
“…MOF-253 was synthesized through solvothermal reactions between Al­(NO 3 ) 3 ·9H 2 O and H 2 bpydc (Figure A). Powder X-ray diffraction (PXRD) studies demonstrated the synthesis of MOF-253 as crystalline white powders, and thermal gravimetric analysis (TGA) supported the chemical formula of Al­(OH) (bpydc) (Figure S2). The treatment of MOF-253 with FeCl 2 in tetrahydrofuran afforded the pre-catalyst 1-pre , which was suspended in methanol and oxidized under an O 2 atmosphere to give the MOF catalyst 1 (Figure B).…”
Section: Resultsmentioning
confidence: 95%
“…The reaction conditions, including temperature, dosage of the catalyst, and solvent, were adjusted for the improvement of selectivity of styrene to styrene oxidation, but there was no obvious effect. However, for these typical catalytic reactions, the oxidation atmosphere is one of the important factors for the selectivity of the oxidation products . Herein, when O 2 was replaced by the air, the styrene oxide was obtained as the major product with high selectivity (88%), yet these reactions needed longer time (>10 h) to accomplish (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…MOFs are usually classified as uniform heterogeneous catalysts, a subclass of single-site heterogeneous catalysts, as the homogeneously distributed unsaturated vacancies of the inorganic node can play the role of catalytic active sites. Alternately, the organic linkers of MOFs can be pre-synthetically or post-synthetically modified with different functional groups, and the active sites can be controllably introduced into the resulting mixed-linker MOFs, , which combine the advantages of both homogeneous and heterogeneous catalysts, also facilitate the development of quasimolecular heterogeneous catalysts. The catenation or interpenetration of frameworks, cavity and aperture expansion in the modification process, as well as painful and multistep organic synthesis remain as the main challenges for the preparation of mixed-linker MOF catalysts. , …”
Section: Introductionmentioning
confidence: 99%